Creativity Center for Child-Friendly Settlements in Kampung Hamdan-Sukaraja With Behavioral Architecture Approach - Rudolf Sitorus; Sania Ariany Siregar (International Journal of Architecture and Urbanism, 2021)
Abstract.Childhood is a phase of human growth that is very important in the growth of one's soul. One of the factors for a person’s character building is creativity that can be formed early on. Children's creativity can be provided by informal education for children through their families and environment. Meanwhile, children in this age of technological development are often given gadgets by their parents, so that children today prefer digital games, which can trigger apathy towards others and reduced creativity space for children. Therefore, the aim is to design a Creativity Center for Child-Friendly Settlements in KampungHamdan-Sukaraja to provides a platform for the development of children's creativity and interest through play and learning activities by presenting social values and local cultural values. This Creativity Center uses the problem-solving methodology approach to solve existing problems, starting from the formulation stage, location surveys, data collection, literature studies, and comparative studies. The Children's Creativity Center is designed simply in terms of material use and affordable handling costs for the community of Kampung Hamdan-Sukaraja. The Creativity Center uses a Behavioral Architecture concept that makes each space designed to be comfortable and safe according to children’s needs and this expected to benefit for providing child-friendly spaces in Kampung Hamdan-Sukaraja as a child-friendly settlement in Medan City for increasing children's creativity